High-resolution ice-core analyses identify the Eldgjá eruption and a cluster of Icelandic and trans-continental tephras between 936 and 943 CE - Hutchison, William; Gabriel, Imogen; Plunkett, Gill; Burke, Andrea; Sugden, Patrick J.; Innes, Helen; Davies, Siwan; Moreland, William M.; Krüger, Kirstin; Wilson, Rob; Vinther, Bo M.; Dahl-Jensen, Dorthe; et al. (Journal of Geophysical Research: Atmospheres, 2024)
Funding: W. Hutchison is funded by a UKRI Future Leaders Fellowship (MR/S033505/1). I. Gabriel and M. Sigl are supported by the European Research Council Grant under the European Union's Horizon 2020 research and innovation program (820047). I. Gabriel received funding from the Swiss Polar Institute and BNP Paribas Swiss Foundation. A. Burke is supported by a Leverhulme Trust Prize (PLP-2021-167). The St Andrews EPMA was supported by the EPSRC Light Element Analysis Facility Grant EP/T019298/1 and the EPSRC Strategic Equipment Resource Grant EP/R023751/1. K. Krüger and M. Sigl acknowledge funding for this study by the Research Council of Norway/University of Oslo Toppforsk project “VIKINGS” with the Grant 275191. R. Wilson is supported by the Natural Environment Research Council project Vol-Clim (NE/S000887/1). The Eldgjá eruption is the largest basalt lava flood of the Common Era. It has been linked to a major ice-core sulfur (S) spike in 939–940 CE and Northern Hemisphere summer cooling in 940 CE. Despite its magnitude and potential climate impacts, uncertainties remain concerning the eruption timeline, atmospheric dispersal of emitted volatiles, and coincident volcanism in Iceland and elsewhere. Here, we present a comprehensive analysis of Greenland ice-cores from 936 to 943 CE, revealing a complex volatile record and cryptotephra with numerous geochemical populations. Transitional alkali basalt tephra matching Eldgjá are found in 939–940 CE, while tholeiitic basalt shards present in 936/937 CE and 940/941 CE are compatible with contemporaneous Icelandic eruptions from Grímsvötn and Bárðarbunga-Veiðivötn systems (including V-Sv tephra). We also find four silicic tephra populations, one of which we link to the Jala Pumice of Ceboruco (Mexico) at 941 ± 1 CE. Triple S isotopes, Δ33S, spanning 936–940 CE are indicative of upper tropospheric/lower stratospheric transport of aerosol sourced from the Icelandic fissure eruptions. However, anomalous Δ33S (down to −0.4‰) in 940–941 CE evidence stratospheric aerosol ...